Current Practice in Fluvial Geomorphology (IntechOpen, 2021)
Amid increasing interactions with other disciplines and technical advances for detecting, monitoring, and modeling fluvial landscape origin, dynamics, and diversity, a number of scientific works have come out and nested in globally recognized edited books. This book is an attempt in this regard, where a few precise regular research works from diverse disciplinary expertise from around the globe are compiled as chapters. In this collective effort, the application of geoinformatics, field data on natural rivers, instrumentation, use of analytic tools, scientific techniques, numerical models, case studies, illustrations, etc. in understanding formative processes and appraising fluvial landscapes will hopefully provide insight into the current practice of fluvial geomorphology and may guide fruitful and coherent scientific enquiry into the field.